Enhanced Therapeutic Efficacy in Cancer Patients by Short-term Fasting: The Autophagy Connection - van Niekerk, Gustav; Hattingh, Suzèl M.; Engelbrecht, Anna-Mart (Frontiers in Oncology, 2016)
Preclinical studies suggest that fasting prior to chemotherapy may be an effective strategy to protect patients against the adverse effects of chemo-toxicity. Fasting may also sensitize cancer cells to chemotherapy. It is further suggested that fasting may similarly augment the efficacy of oncolytic viral therapy. The primary mechanism mediating these beneficial effects is thought to relate to the fact that fasting results in a decrease of circulating growth factors. In turn, such fasting cues would prompt normal cells to redirect energy towards cell maintenance and repair processes, rather than growth and proliferation. However, fasting is also known to up-regulate autophagy, an evolutionarily conserved catabolic process that is up-regulated in response to various cell stressors. Here we review a number of mechanisms by which fasting-induced autophagy may have an impact on both chemo-tolerance and chemo-sensitization. Firstly, fasting may exert a protective effect by mobilizing autophagic components prior to chemo-induction. In turn, the autophagic apparatus can be repurposed for removing cellular components damaged by chemotherapy. Autophagy also plays a key role in epitope expression as well as in modulating inflammation. Chemo-sensitization resulting from fasting may in fact be an effect of enhanced immune surveillance as a result of better autophagy-dependent epitope processing. Finally, autophagy is involved in host defense against viruses, and aspects of the autophagic process are also often targets for viral subversion. Consequently, altering autophagic flux by fasting may alter viral infectivity. These observations suggest that fasting-induced autophagy may have an impact on therapeutic efficacy in various oncological contexts.